Pengaruh Strategi Pembelajaran Inkuiri Sosial terhadap Prestasi Belajar Pendidikan Agama Hindu Kelas VIII SMP Negeri 1 Penebel - I Made Sukma Muniksu (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2021)
The use of social inquiry learning strategies in the teaching and learning process is prioritized for teaching Hindu religious education subjects in junior high schools. Students are bored in facing the teaching and learning process with the lecture method, so the teacher must be able to teach using social inquiry learning strategies to attract students' learning interest and interest because students are invited to think critically. This gap is then examined regarding the use of social inquiry learning strategies in Hindu religious education in class VIII SMP Negeri 1 Penebel. The objectives of this study were (1) to find out about social inquiry learning strategies and learning achievement of Hindu religious education class VIII SMP Negeri 1 Penebel and (2) To determine the effect of using social inquiry learning strategies on the learning achievement of Hindu religious education students of class VIII SMP Negeri 1 Penebel. This study uses two research variables, namely the independent variable (independent variable) and the dependent variable. The population taken from this study were students of class VIII SMP Negeri 1 Penebel who attended Hinduism lessons with a sample of 73 students using random sampling techniques. Collecting data using a test method in the form of multiple choice tests. Analysis of hypothesis testing using the t-test formula. The results showed that (1) This study found that the implementation of the social inquiry learning strategy at SMP Negeri 1 Penebel was running quite well. It can be seen from the 78 - 83 interval class that gets the highest number of frequencies, namely 34 with a percentage of 46.6% with a fairly good category. (2) This study found that the learning achievement of Hindu religious education in grade VIII students at SMP Negeri 1 Penebel was quite good. It can be seen from the 78 - 86 interval class to get the highest number of frequencies, namely 55 with a percentage of 71.4% with a fairly good category.Keywords: Social Inquiry Learning Strategy, Hindu Religious Education